Autores - Rivas, Ramón D. (Kóot, 2016)
Carmen Molina TamacasRubén FúnezIliana Stephanie Arias SalegioLuis Alberto AmbroggioPablo de Jesús Castro H.Rhina Toruño-HaenslyRamón D. RivasJulio MartínezCarlos OseguedaDavid Hernández